Unlike adults, children and adolescents show predominantly increased neural activation to social exclusion by members of the opposite gender - Bolling, Danielle Z. (Soc Neurosci, 2015)
The effects of group membership on brain responses to social exclusion have been investigated in adults, revealing greater anterior cingulate responses to exclusion by members of one’s in-group (e.g. same-gender). However, social exclusion is a critical aspect of peer relations in youth and reaches heightened salience during adolescence, a time when social anxiety disorders are also emergent. While the behavioral and neural correlates of social exclusion in adolescence have been extensively explored, the effects of group membership on peer rejection are less clear. The current study used functional magnetic resonance imaging (fMRI) to investigate the differential neural correlates of being excluded by peers of one’s same-versus opposite-gender during an online ball-toss game. Participants were a group of typically developing children and adolescents (7–17 years). As predicted, anterior cingulate cortex showed a main effect of social exclusion versus fair play. However, unlike a previous adult study, this region did not show increased activation to same-gender exclusion. Instead, several regions differentiating same-versus opposite-gender exclusion were exclusively more sensitive to exclusion by one’s opposite gender. These results are discussed in the context of adolescent socioemotional development.